Export, Import and Economic Growth: Evidence from Sri Lanka - Velnampy, T.; Achchuthan, S. (My University, 2014)
This research focuses on the research question as what extent the export and import influence on Economic growth in the Sri Lankan Perspective. Data on the economic growth, export and import from the year 1970 to 2010 were collected for the study purpose. The results revealed that, the export and import have the significant positive relationship with each other, and also, both export and import have the significant impact on the economic growth. Further, the export and import have been associated by 98 percent, which denotes that, there is strong positive association between export and import. We have suggested that, the small medium enterprises should be motivated towards export orientation. Meantime, the restrictions in the import of the raw materials to the industries should be implemented in the flexible way through the fiscal and monetary policy. In the further research, the performance of the external sector should be tested in the srilankan context to identify the cues in the export and import sector development and its policy framework.
Keywords: Export; Import and Economic Growth